DETERMINANTS OF INCOME INEQUALITY IN INDONESIAN PROVINCES: EVIDENCE FROM SYSTEM GMM - Anika Cahya Safitri; Dedy Yuliawan (Journal Informatic, Education and Management (JIEM), 2026)
Income inequality remains a critical structural challenge in Indonesia, particularly across the major islands of Sumatra, Java, and Kalimantan. This study analyzes the determinants of income inequality in 21 provinces across these three islands from 2015 to 2024, using the Generalized Method of Moments (GMM) dynamic panel approach developed by Arellano and Bond (1991). The dependent variable is the Gini Ratio, while the independent variables consist of Economic Growth (GRDP per capita), Open Unemployment Rate (OUR), Mean Years of Schooling (MYS), and Poverty Rate. The study employs a dynamic panel model to address endogeneity problems and capture the persistence of income inequality over time. Results indicate that the lagged Gini Ratio, the Open Unemployment Rate, Mean Years of Schooling, and Poverty Rate have statistically significant effects on income inequality, while Economic Growth does not show a significant direct effect. The GMM model's validity is confirmed through the Arellano-Bond AR(2) test and the Hansen overidentification test. These findings underscore the importance of inclusive growth policies, expanded educational access, and poverty reduction programs to achieve more equitable income distribution across Indonesian provinces.